Optimization of the treatment of patients with proliferative diseases of the uterus - I A Lapina; N I Nasyrova (IP Berlin A.V., 2015)
Proliferative diseases of the uterus, including uterine fibroids, endometriosis, endometrial hyperplasia are characterized by a rather wide distribution in the structure of gynecological pathology offset towards the younger population. These diseases are often combined in the same patient, which complicates the treatment of this group of patients and increases the frequency of relapses.